Simulation of fire resistance behaviour of pultruded GFRP beams – Part I: Models description and kinematic issues. (1st March 2018) - Morgado, T.; Silvestre, N.; Correia, J.R.
Abstract: This two-part paper presents a numerical study about the fire resistance behaviour of pultruded GFRP profiles with square tubular cross-section subjected to bending and the ISO 834 time-temperature curve. The first paper deals with the development of numerical and analytical models and the discussion of relevant kinematic issues, including the evolution of beam deflection and position of neutral axis with the fire exposure time. The second part [1] reports an in-depth investigation on the side of static issues, which include the evolution of stress distributions and failure initiation with the fire exposure time. In the present paper, three–dimensional finite element models were developed to simulate fire resistance tests previously conducted by the authors on GFRP beams, in which different degradation curves were considered for compressive, tensile and shear moduli, based on experimental data. In these numerical simulations, both effects of varying the assignment of material properties (depending on the position of neutral axis) and of considering different thermal expansion coefficients were taken into account, and some conclusions were drawn on their influence on mid-span deflection evolutions. Since no failure criterion was implemented, both models were not able to reproduce the failure of the beams, but the overall tendency of the numerical results was consistent with the experimental data. Alongside the numerical study, analytical models based on Timoshenko beam theory were also developed and allowed obtaining accurate predictions of the mid-span deflection evolution of the GFRP beams; the analytical results were in close agreement with the numerical ones and also with the experimental data.